DEVELOPING VILLAGE GOVERNMENT CAPACITY IN REALIZING GOOD GOVERNANCE IN BANYUMAS DISTRICT - Indranika, Devit Bagus; Weningsih, Sri (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The village government apparatus is one of the most important components in moving government at the village level. Success in running government at the village level can be based on the good capacity of the village government within it. Through developing the capacity of village governments, the goal of realizing good governance will be achieved. The aim of this research is to find out how well the village government's capacity development is in realizing good governance in Banyumas Regency. The method used is a survey with data collection in the form of questionnaires, observation and documentation. The sampling technique uses a multi stage sampling technique. Data analysis used used frequency distribution, mean and standard deviation. The research results show that the development of village government capacity in realizing good governance in Banyumas Regency is mostly in the quite good category with a percentage of 48.1 percent. This is demonstrated by the existence of three indicators, including human resource development, organizational strengthening, and institutional reform.